1991
DOI: 10.1210/jcem-73-2-281
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Endocrine Neoplasia Type 1: A 10-Year Prospective Screening Study in Four Kindreds*

Abstract: A total of 80 individuals in 4 kindreds with multiple endocrine neoplasia type 1 (MEN 1) have been subjected to repeated biochemical screening during a 10-yr period with the principal aim being to analyze characteristics of the developing pancreatic lesion. Age at presentation of the MEN 1 trait averaged 18 yr in 7 previously unaffected individuals, and this effect of the screening procedure represented a lowering by almost 2 decades. Pancreatic endocrine involvement was recognized at a mean age of 25 yr and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
172
0
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(185 citation statements)
references
References 28 publications
10
172
0
3
Order By: Relevance
“…distinguishing clinical features of the four patients who lacked adrenal hyperplasia, all had hyperparathyroidism, three had pituitary tumours and three had pancreatic endocrine tumours. A previous study by Skogseid et al (16) suggested that adrenal enlargement was associated with the presence of pancreatic endocrine tumours. This does not appear to be evident within our cohort; three out of four with normal adrenal size and 7 out of 24 with adrenal hyperplasia had confirmed pancreatic endocrine tumours.…”
Section: Discussionmentioning
confidence: 92%
“…distinguishing clinical features of the four patients who lacked adrenal hyperplasia, all had hyperparathyroidism, three had pituitary tumours and three had pancreatic endocrine tumours. A previous study by Skogseid et al (16) suggested that adrenal enlargement was associated with the presence of pancreatic endocrine tumours. This does not appear to be evident within our cohort; three out of four with normal adrenal size and 7 out of 24 with adrenal hyperplasia had confirmed pancreatic endocrine tumours.…”
Section: Discussionmentioning
confidence: 92%
“…1 However, it is accepted that the earlier the identification of MEN1 neoplasias, the better the clinical management of this disease. 30,31 As recommended by the MEN Consensus, the suggested approach for patients with MEN1 is based on periodical surveillance of MEN1-related neoplasias that should begin as early as 5 to 20 years of age.…”
Section: Pituitary Tumors In Men1mentioning
confidence: 99%
“…Exceptions to this are the carcinoids of the appendix, which occur with the highest incidence below 30 years of age, followed by the age group between 30 and 49 years. MEN-1 patients may have a clinical onset 15 years earlier than patients with sporadic cases (3,4).…”
Section: Epidemiology Of Ne Tumoursmentioning
confidence: 99%
“…No exact figures for incidence are available, whereas a prevalence of 0.2 has been reported. It is a general belief that MEN-1 is largely under-diagnosed in most countries (4).…”
Section: Men-1mentioning
confidence: 99%
See 1 more Smart Citation